49.4k views
4 votes
‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 +

‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 + ‐9−(‐12)= ‐9 +-example-1
User Doug Hauf
by
5.7k points

2 Answers

4 votes

Answer:

i am soooooooooooooooooo counfused

User Drew Schuster
by
4.9k points
3 votes

Answer:

12

Explanation:

Left:

Simplify the following:

-9 - -12

-(-12) = 12:

-9 + 12

-9 + 12 = 3:

Answer: 3

______________________

Right:

Do the following addition:

-9 + 12

The number -9 is negative. Start from 0 and move 9 to the left:

Show the addition of 12 to -9. Start from the end of the previous arrow and move 12 to the right:

The final arrow is pointed at 3. This is the answer:

Answer: 3

User Sachin Mandhare
by
6.2k points